Warung Makan di Pantai Melasti, Bali dalam Kajian Lanskap Linguistik: Dari Tipat Cantok sampai Burger - I Gusti Ngurah Agung Suprastayasa; Ni Kade Juli Rastitiati (JURNAL GASTRONOMI INDONESIA, 2023)
The linguistic landscape has attracted the interest of many language researchers recently. One area of study that has not received much attention is the linguistic landscape of restaurants. Therefore, this study aims to analyze the linguistic landscape of food stalls in Melasti Beach, Bali. Data was obtained by taking photos using a cell phone camera against signboards, banners and menu lists displayed in front of the restaurant. A total of 43 photos were collected and there were 144 items analyzed. then categorized based on the language used. The results of the study found that the use of language in the linguistic landscape at Melasti Beach was dominated by the use of Indonesian and followed by English and other foreign languages. There is the phenomenon of bilingualism and multilingualism. This linguistic landscape is in line with tourists visiting Melasti Beach.